Clinical and radiological outcomes of jumbo cup in revision total hip arthroplasty: A systematic review - Wang, Qiuyuan; Wang, Qi; Liu, Pei; Ge, Juncheng; Zhang, Qidong; Guo, Wanshou; Wang, Weiguo (Frontiers in Surgery, 2022)
Introduction Many studies have reported the clinical outcomes of a jumbo cup in revision total hip arthroplasty (rTHA) with acetabular bone defect. We conducted a systematic review to access the survivorship and clinical and radiological outcomes of a jumbo cup in rTHA. Methods A systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A comprehensive literature search from PubMed, MEDLINE, EMBASE, and the Cochrane Database of Systematic Reviews was performed with the keywords (“revision” OR “revision surgery” OR “revision arthroplasty”) AND (“total hip arthroplasty” OR “total hip replacement” OR “THA” OR “THR”) AND (“jumbo cup” OR “jumbo component” OR “extra-large cup” OR “extra-large component”). Studies reporting the clinical or radiological outcomes were included. The basic information and radiological and clinical results of these studies were extracted and summarized for analysis. Results A total of 19 articles were included in the systematic review. The analysis of clinical results included 953 hips in 14 studies. The re-revision-free survivorship of the jumbo cup was 95.0% at a mean follow-up of 9.3 years. Dislocation, aseptic loosening, and periprosthetic joint infection were the top three complications with an incidence of 5.9%, 3.0%, and 2.1%, respectively. The postrevision hip center was relatively elevated 10.3 mm on average; the mean postoperative leg-length discrepancy was 5.4 mm. Conclusion A jumbo cup is a favorable option for acetabular bone defect reconstruction in rTHA with satisfying survivorship and acceptable complication rates.